'You don't need to love us': Civil-Military Relations in Afghanistan, 2002–13. Issue 2 (6th August 2013) - Haysom, Simone; Jackson, Ashley
In recent years the growing involvement of militaries in the delivery of assistance in conflict-affected areas under the rubric of stabilisation or comprehensive approaches has become a key concern for humanitarian agencies, raising questions about the adequacy of existing guidance and current approaches to civil-military coordination. In order to better understand the challenges of principled and effective dialogue between military forces and independent humanitarian actors in the context of combined international and national military forces pursuing stabilisation, this article charts the evolution of the civil-military dialogue in Afghanistan from 2002 until 2012. Drawing on semi-structured interviews with a range of former staff of aid agency, military, and donor organisations who were present in Afghanistan in this period as well as audits, official guidelines, and other written documents, this article provides an analytical overview of the development of stabilisation approaches in Afghanistan and the strategies aid agencies pursued in response, in particular the trajectory of mechanisms for structured dialogue. Lastly, it identifies several implications that can be drawn from this experience for aid agencies, NATO, and troop contributing nations.